Сучасний стан питання розробки нормативів електроспоживання на зернопунктах - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina (My University, 2005)
UK: У роботі проаналізовані існуючі методи нормування електроспоживання на післязбиральну обробку зерна з метою розробки нової методики визначення норм витрат електроенергії на зернопунктах. EN: In work existing methods of normalization of a power consumption on processing of a grain are analysed with the purpose of development of a new technique of definition of norms of expenses of the electric power on grain items.
Modern condition of a question of development of specifications of a power consumption on grain items
Keywords: питомі норми електроспоживання; раціональне використання електроенергії; нормування електроспоживання; методика нормування електроспоживання